A yeast display immunoprecipitation screen for targeted discovery of antibodies against membrane protein complexes. Issue 5 (26th November 2019) - Lajoie, Jason M; Cho, Yong Ku; Frost, Dustin; Bremner, Samantha; Li, Lingjun; Shusta, Eric V
Abstract: Yeast display immunoprecipitation is a combinatorial library screening platform for the discovery and engineering of antibodies against membrane proteins using detergent-solubilized membrane fractions or cell lysates as antigen sources. Here, we present the extension of this method for the screening of antibodies that bind to membrane protein complexes, enabling discovery of antibodies that target antigens involved in a functional protein-protein interaction of interest. For this proof-of-concept study, we focused on the receptor-mediated endocytosis machinery at the blood-brain barrier, and adaptin 2 (AP-2) was chosen as the functional interaction hub. The goal of this study was to identify antibodies that bound to blood-brain barrier (BBB) membrane protein complexes containing AP-2. Screening of a nonimmune yeast display antibody library was carried out using detergent-solubilized BBB plasma membranes as an antigen pool, and antibodies that could interact with protein complexes containing AP-2 were identified. Downstream characterization of isolated antibodies confirmed targeting of proteins known to play important roles in membrane trafficking. This functional yeast display immunoprecipitation screen may be applied to other systems where antibodies against other functional classes of protein complexes are sought.